Assessment of the efficacy of successive endocrine therapies in hormone receptor–positive and HER2-negative metastatic breast cancer: a real-life multicentre national study. (September 2019) - Le Saux, Olivia; Lardy-Cleaud, Audrey; Frank, Sophie; Debled, Marc; Cottu, Paul H.; Pistilli, Barbara; Vanlemmens, Laurence; Leheurteur, Marianne; Lévy, Christelle; Laborde, Lilian; Uwer, Lionel; D'hondt, Veronique; et al.
Abstract: Background: For luminal metastatic breast cancer (MBC), endocrine therapy (ET) is the recommended initial treatment before chemotherapy. Our objective was to evaluate the efficacy of multiple ET lines in a real-life study. Methods: The Breast Cancer Epidemiological Strategy and Medical Economics (ESME) project analysed data from all patients with systemic treatment for MBC initiated between 2008 and 2014 in one of the 18 French Comprehensive Cancer Centres. The primary end-point was the successive progression-free survival (PFS) evaluation. Results: The ESME research programme included 9921 patients with hormone receptor–positive (HR+)/human epidermal growth factor receptor 2 (HER2) negative (HER2-) MBC. Before any chemotherapy, 4195 (43.4%), 1252 (29.8%) and 279 (6.6%) patients received one, two or three ET ± targeted therapy, respectively. The median PFS for first-, second- and third-line ET ± targeted therapy was 11.5 (95% confidence interval [CI], 10.8–12.1), 5.8 (95% CI, 5.3–6.1) and 5.5 (95% CI, 4.6–6.3) months, respectively. In a multivariate analysis, time from diagnosis to metastatic recurrence (P < 0.0001), presence of symptoms at metastatic relapse ( P = 0.01), number of metastatic sites ( P = 0.0003) and their localisation ( P < 0.0001) were prognostic factors for PFS1. Duration of previous PFS was the only prognostic factor for subsequent PFS (10% threshold). Ten percent of the patients showed long-term response to ET, with a total treatment duration before chemotherapy ≥43.6 months. Conclusions: Median PFS in our HR+/HER2- real-life cohort is similar to median first-line PFS reported in clinical trials, regardless of ET used as second- and third-line treatment. Despite the international consensus on early initiation of ET, the latter is not prescribed in most of the cases. Patients with a low tumour burden may achieve prolonged response on ET. Highlights: Contrary to guidelines, endocrine therapy was prescribed to a minority of patients. In our real-life cohort, median PFS compared favourably with clinical trial results. Patients with a low tumour burden may achieve prolonged response.